NutriTalk: Nutrition Intervention by Experts to Reduce the Impact of Stunting Through Mobile Based Applications Using Agile Method - Kurniasari, Arvita Agus; Olivia, Zora; Suryana, Arinda Lironika; Widiyawati, Agatha; Maria Rosiana, Nita (Jurnal Teknokes, 2023)
The prevalence of childhood stunting, a pervasive global health concern primarily attributed to persistent malnutrition, underscores an urgent need for intervention. In Indonesia, where stunting rates are alarmingly high, with approximately 27.6% of children under five affected, innovative solutions are imperative. This study introduces "Nutri Talk," a mobile application developed using Agile Methodology to revolutionize nutritional consulting services. The application facilitates seamless communication with nutrition specialists, offering evidence-based information and personalized consultations to empower parents in making informed dietary decisions for their children. The application demonstrates robust functionality and user satisfaction through rigorous testing, including Boundary Value Analysis (BVA) and User Acceptance Testing (UAT). "Nutri Talk" stands poised to mitigate the long-term impacts of stunting, leveraging technology to enhance nutritional outcomes. This research advocates for a comprehensive approach to combat stunting, combining mobile technology advancements with targeted interventions, ultimately contributing to improved childhood nutrition and development.